2007
DOI: 10.1007/s11096-007-9130-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring elements of interprofessional collaboration between pharmacists and physicians in medication review

Abstract: In medication review involving community pharmacists and physicians, there is an underlying assumption that if community pharmacists provide evidence based pharmacotherapeutic recommendations, physicians, in turn, will implement these recommendations. However, although in general medication review has been shown to improve the quality of medicine use, medication management plans arising from the medication review process are not always implemented. There is a need for better understanding of the factors that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 11 publications
4
57
0
Order By: Relevance
“…In our model, this was done face to face. This method appears to be the most effective if a medication review is to be successfully implemented [9]. However, it is not possible to draw any definitive conclusions about the higher acceptance rate in our study, since the type (actual or potential) and the method of communicating were not described in detail in the other studies.…”
Section: Discussionmentioning
confidence: 57%
“…In our model, this was done face to face. This method appears to be the most effective if a medication review is to be successfully implemented [9]. However, it is not possible to draw any definitive conclusions about the higher acceptance rate in our study, since the type (actual or potential) and the method of communicating were not described in detail in the other studies.…”
Section: Discussionmentioning
confidence: 57%
“…Drug-related problems found, % (95 % CI) 31 (29)(30)(31)(32)(33) Interventions, n (%) 537 (31) Acceptance rate for Interventions…”
Section: Timingmentioning
confidence: 99%
“…How interventions are communicated between pharmacists and physicians highly affect acceptance rates, and face-to-face communication has been recognised to be an important factor leading to the highest acceptance rate [29][30][31]. However, this form of communication can be difficult in acute wards with a high-paced workflow.…”
Section: Introductionmentioning
confidence: 99%
“…Whether GPs consider the life-world problems in the further management of the disease remains to be seen as different studies have shown considerable variations regarding the extent to which GPs follow the recommendations of pharmacists having conducted medication reviews [9,10]. Nevertheless, the study showed that a medication review program based on the introduced interview guide taking place usually in the patients' home is a feasible way to build a bridge between the technical world of health care providers and the life-world perspective of patients.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Results of medication reviews conducted by pharmacists have shown significant reductions of blood glucose, blood pressure and blood lipids as well as an increase in patients' knowledge of their therapy and adherence [2,[6][7][8][9]. Chen et al [10] has however called for further investigation into factors that influence the outcome of medication review programs [10].…”
mentioning
confidence: 99%